The Importance of Wall Apposition in Flow Diverters. Issue 3 (4th April 2018) - Aquarius, René; de Korte, Antonius; Smits, Debby; Gounis, Matthew; Verrijp, Kiek; Driessen, Léon; Leenders, William; de Vries, Joost
Abstract: BACKGROUND: It is assumed that high pore densities in flow diverters (FDs) are beneficial for intracranial aneurysm (IA) healing. However, various animal studies are not conclusive on the issue, suggesting that other factors are in play. One important factor might be wall apposition. OBJECTIVE: To (1) determine the relationship between FD pore density and aneurysm occlusion, and (2) determine the relationship between FD wall apposition and aneurysm occlusion. METHODS: Saccular aneurysms were microsurgically created in the aorta of 36 Wistar rats. Twelve rats received a low pore density FD (10 pores/mm 2 ), 12 rats received a high pore density FD (23 pores/mm 2 ), and the remaining 12 rats served as a control group. Six animals from each group were sacrificed 1 and 3 mo after surgery. We determined aneurysm occlusion, the number of struts not in contact with the aorta wall, and the average distance from malapposed struts to aorta wall through histology. RESULTS: No significant differences were found in aneurysm occlusion between the low pore density and high pore density groups ( P  > .05) after 1 and 3 mo of follow-up. The average number of malapposed struts was lower for the occluded aneurysm group (4.4 ± 1.9) compared to the nonoccluded aneurysm group (7.7 ± 2.6, P  < .01). The average distance between malapposed struts and parent artery wall was lower for the occluded aneurysm group (33.9 μm ± 11.5 μm) than for the nonoccluded aneurysm group (48.7 μm ± 18.8 μm, P  < .05). CONCLUSION: Wall apposition is more important than pore density for aneurysm occlusion.